Caracterização de compostos bioativos e avaliação dos efeitos do extrato hidroetanólico do cafeeiro (Coffea Arabica) sobre o perfil lipídico, estresse oxidativo e agregação plaquetária em ratos dislipidêmicos - Simões, Mário Henrique Souza (2014)
Atherosclerosis has occupied a prominent place among the risk factors for developing cardiovascular disease, which in turn, constitute a major cause of death worldwide. Dyslipidemias, oxidative stress and platelet activation are important risk factors for atherosclerosis. Thus, the use of statins in combination with antioxidants, anticoagulants, antiplatelet, antiinflammatory or vasodilators has been suggested to control and even prevent atherosclerotic processes. As the coffee beverage, its leaves has a diversified chemical composition, containing different chemicals, some associated with human health, such as chlorogenic acid. This work has as main objective to evaluate the antioxidant potential of dried extract of leaves of Coffea arabica and its possible effects on the lipid profile, liver function, renal function and platelet aggregation in dyslipidemic mice. The collected leaves were dried in an oven, pulverized in a Wiley mill and the extract was obtained by the method of exhaustive extraction of simple percolation in water-alcohol solution 70% (V / V), followed by evaporation under reduced pressure and lyophilization. Phytochemical screening was done by determining the concentration of phenols Folin & Ciocaulteau and analysis of the extract by mass spectrometry with electrospray ionization in negative and positive ways. The antioxidant potential in vitro was assessed by determining the ability of scavenging DPPH radicals. Rats "Wistar" rats (300 ± 25g) were divided into four groups: control, extract, extract-dyslipidemic and dyslipidemic, with the latter two received Triton WR-1339, ip To induce dyslipidemia. Serum urea, total cholesterol, triglycerides and HDL cholesterol were determined by enzymatic methods and creatinine concentration was determined by the alkaline pricrate method. The activity of AST and ALT were determined by the method of Reitman and Frankel and alkaline phosphatase activity by the method of Roy with modifications. Lipid peroxidation was determined in plasma and aortic homogenates by determining the concentration of thiobarbituric acid reactive substances (TBARS) by fluorimetry substances. Platelet aggregation was evaluated in platelet-rich plasma by turbidimetry. The concentration of total phenols was equal to 6.817 ± 0.133 g EAG/100 g of extract. The data set provided by the mass spectrum suggested that the extract under study has in its phenolic composition as quinic acid, rutin and chlorogenic acid. The extract showed maximum scavenging activity of DPPH radicals of 90.1% at a concentration of 0.16 mg / ml, comparable to BHT standards (95.5%) and gallic acid (88.2%). No significant change was observed in the levels of urea and creatinine as well as in AST, ALT and alkaline phosphatase activities. The animals treated with Triton WR 1339 showed an increase in serum levels of cholesterol (TC) and triglycerides in TBARS concentration in plasma and aorta as well as platelet aggregation. The group of animals treated with the extract was not able to induce changes in the lipid profile, but showed a significant decrease in TBARS concentration and platelet aggregation compared with dyslipidemic animals not treated with the extract. These results suggested that the extract study has a beneficial effect on the prevention of atherosclerosis by preventing the increase in lipid peroxidation in plasma and aorta as well as platelet aggregation in dyslipidemcs rats.